Risk-return analysis. the theory and practice of rational investing - Markowitz, Harry M., 1927-2023 (McGraw Hill Education, 2016)
The Nobel Prize-winning Father of Modern Portfolio Theory provides new insights and methods to help you build a lasting portfolio